Peranan Gerakan Apostolik Dalam Pelayanan Para Imam dan Kaum Awam Beriman - & Fransiskus Heryman Surya Gadur, Angelo Luciani Moa Dosi Woda (Jurnal Alternatif Wacana Ilmiah Interkultural, 2023)
In the life of the Church, especially in the concrete pastoral experience for the people both in the Parishes and religious communities, we found a unique phenomenon, that is the lay Catholic faithful less involved in the office of the Church’s apostolic. The fundamental question is our Church ministry only carried out exclusively by clergy and religious people? How about the role of the lay Catholic people in the mission of the Church? In a way to answer those questions, we try to reflect regarding the faith of the Catholic Church on the office of the Church’s Apostolic in the ministry of the priests and the lay Catholic faithful. For that reason, we investigate the Bible and the Sacred Tradition and especially the work of the Holy Spirit in the Church’s Evangelization. That means we shall investigate the development of faith regarding the Apostolic’s Succession. Obviously, there is a living communion between Local Church and the renewal of the religious life. Simultaneously, there is a warm communion between Universal and Local Church. This theological research reveals that an urgent need to comprehend in a new way the relation between Christology and Pneumatology. The consequences are that we eventually detect the essential relation of the organic unity between hierarchical and charismatic dimension in the Catholic Church. Thus, we shall recognize the important role of the lay people in the life of the Church. In this way, we could understand the obedience to the Holy Spirit and to Church’s hierarchy. Dalam hidup menggereja, terutama dalam pengalaman konkret pastoral bagi umat di Paroki maupun di komunitas religius, kita menjumpai fenomena unik, bahwa umat awam beriman Katolik kurang terlibat dalam karya apostolik Gereja. Pertanyaan mendasarnya ialah apakah pelayanan Gereja hanya ekslusif dilaksanakan oleh kaum klerus dan kaum religius saja? Bagaimana peranan kaum awam beriman Kristiani dalam misi Gereja? Dalam rangka menjawab pertanyaan tersebut, kami mencoba mengelaborasikan, menafsirkan, dan merefleksikan iman Gereja tentang Karya Apostolik Gereja dalam Pelayanan Imam dan Kaum Awam Beriman Katolik. Karena itu, kami menyelidiki ajaran Kitab Suci dan Tradisi Suci, serta Karya Roh Kudus dalam Evangelisasi Gereja. Itu berarti menelusuri perkembangan ajaran iman tentang panggilan dan pelayanan para rasul. Kemudian, kita temukan adanya penerusan tak terputus Suksesi Apostolik dalam Gereja Perdana. Karya Apostolik itu terus berlangsung sepanjang zaman hingga saat ini. Terbukti dengan ada persekutuan antara Gereja Lokal dengan pembaruan hidup religius. Tanpa melupakan kesatuan utuh antara Gereja Universal dan Gereja Lokal. Penelitian Teologis menunjukkan bahwa perlu memahami secara baru relasi Kristologis dan Pneumatologis. Konsekuensinya, kita menemukan relasi hakiki kesatuan organis antara dimensi Hierarkis dan Karismatis dalam Gereja. Maka, kita patut bersyukur akan adanya peranan kaum awam beriman dalam Hidup Gereja. Di satu sisi, kaum awam menghormati hierarki Gereja. Tetapi, di lain pihak, hierarki Gereja menjadi sahabat dekat kaum awam. Dengan kata lain, betapa pentingnya ketaatan kepada Roh Kudus sebagai primat utama dan ketaatan kepada hierarki Gereja.